2014
DOI: 10.1111/dme.12589
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of free triiodothyronine with pancreatic β‐cell function in people with prediabetes

Abstract: Free triiodothyronine is associated with both basal and glucose-stimulated insulin secretion in people with prediabetes who are euthyroid; therefore, the regulation of insulin secretion by thyroid hormones is a potentially novel therapeutic target for the treatment of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…In addition, thyroid dysfunction decreases glucose transport in myocytes and increases insulin resistance in muscle and adipose tissue [18,19]. Moreover, recent studies have demonstrated that FT3 can regulate insulin secretion [20,21]. erefore, FT3 may play an important role in glucose metabolism and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thyroid dysfunction decreases glucose transport in myocytes and increases insulin resistance in muscle and adipose tissue [18,19]. Moreover, recent studies have demonstrated that FT3 can regulate insulin secretion [20,21]. erefore, FT3 may play an important role in glucose metabolism and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, regarding human studies, so far there have been few reports connecting T3 levels to pancreatic β cell function in prediabetic and diabetic patients. A multiple linear regression epidemiologic study [ 99 ] showed that free T3 is an independent variable with a positive correlation with all indexes of β cell function in the prediabetes and euthyroid group. In another study [ 100 ], a total of 266 patients with type 2 diabetes and normal thyroid function were recruited in order to study the associations between serum T3, FT3, and acute insulin response (AIR) in type 2 diabetes.…”
Section: Thyroid Hormone Treatment Ameliorates Pancreas Dysfunctiomentioning
confidence: 99%
“…Treatment of hypothyroidism has been revealed to restore insulin sensitivity and the secretion of glucoregulatory hormones [6,48]. The hyperthyroidism is associated with insulin resistance but this high and high-normal thyroid functions are protective to progression of diabetes as the hyperthyroidism causes increased insulin secretion [41,[49][50][51]. In vitro studies suggest that T3 and Thyroid Receptor alfa (TRα) promote proliferation of pancreatic islet cell.…”
Section: *Correspondencementioning
confidence: 99%
“…In vitro studies suggest that T3 and Thyroid Receptor alfa (TRα) promote proliferation of pancreatic islet cell. T3 also stimulates the islet transcription factor Mafa, which contributes to the transition of islets to glucose-responsive insulinsecreting cells, which further improves the insulin secretion in presence of higher free T3 in prediabetics [50][51]. Studies suggest that during hyperthyroidism the release of insulin precursors increases but they are inactive form and due to that insulin degradation rate increases and the half-life of insulin is reduced [52][53].…”
Section: *Correspondencementioning
confidence: 99%